Estimation of dietary AFB1 exposure through the level of AFM1 detected in human urine samples : a preliminary study. - Sabran, Mohd Redzwan; Jamaluddin, Rosita; Abd. Mutalib, Mohd Sokhini (2012)
Aflatoxin B1 (AFB1) is a toxin produced by Aspergillus species of fungi and commonly found contaminating foodstuffs such as cereals, nuts and spices. Once absorbed in the bloodstream, AFB1 is metabolised into aflatoxin M1 (AFM1) and excreted in the urine. This preliminary study aimed to extrapolate the AFM1 level detected in human urine in estimating dietary AFB1 exposure. Twenty-two adults were recruited randomly and morning urine samples were collected. The AFM1 level was measured using direct enzyme-linked immunosorbent assay. AFM1 was detected in all urine samples (mean ± SEM = 0.0421 ± 0.006 ng/ml; 95% CI = 0.0299 – 0.0544 ng/ml). The AFM1 value was back-transformed to estimate dietary AFB1 exposure. The mean estimated dietary AFB1 exposure was 0.028 !g/day/kg BW and it was significantly different between educational level (z = -2.242; p = 0.025) and BMI (χ2 = 6.883; p = 0.032). The estimated dietary AFB1 exposure also showed significant positive correlation with the consumption of powdered milk (r = 0.435; p = 0.021), condensed milk (r = 0.522; p = 0.006) and peanuts (r = 0.390; p = 0.036). It can be postulated that human exposure to aflatoxin may involve many inter-related factors such as dietary habits, environmental and lifestyle factors. Since AFB1 is classified as Group 1 carcinogen by the International Agency for Research on Cancer (IARC), this foodborne contamination could lead to many detrimental health effects. Therefore, findings from this study warrant further investigations to detect the sources and potential consequences of this contaminant exposure in Malaysia.